Association between serum vitamin D and the risk of diabetic kidney disease in patients with type 2 diabetes - Wang, Yujie; Hu, Chenggang; Li, Ying; Liu, Qi; Gao, Lichao; Zhang, Dongmei; Cao, Ling (Frontiers in Medicine, 2024)
Aims This investigation explored the potential correlation between serum vitamin D concentration and diabetic kidney disease (DKD) among patients with type 2 diabetes mellitus (T2DM). Methods This cross-sectional study assessed 4,570 patients with T2DM drawn from the National Health and Nutrition Examination Survey (NHANES) dataset. Restricted cubic splines were utilized to examine the dose–response relationship between serum vitamin D levels and the risk of DKD in patients with T2DM. Serum vitamin D concentrations were divided into quartiles for multivariable logistic regression analysis to evaluate the association between varying serum vitamin D levels and DKD risk in patients with T2DM. Additionally, sex-stratified analyses were conducted to determine consistency of the results. The influence of vitamin D concentrations on mortality risk was assessed using a Cox regression model. Results Of the patients with T2DM, 33% were diagnosed with DKD. Restricted cubic spline plots revealed a U-shaped relationship between vitamin D levels and DKD risk, with a protective effect noted in the mid-range, indicating optimal serum vitamin D concentrations between 59.6 nmol/L and 84.3 nmol/L. The multivariate Cox regression analysis suggested that higher VID levels were associated with a reduced mortality risk, particularly in male patients. Conclusion The regulation and monitoring of serum vitamin D levels within an optimal range may play a pivotal role in the prevention of DKD in patients with T2DM. Public health strategies should emphasize the regular monitoring of vitamin D levels, especially among populations at elevated risk, to mitigate the progression of DKD and decrease the associated mortality rates.